The Influence of Green Marketing and Green Consumers on the Interest in Buying Electric Motorcycles in Cirebon City - Muchamad Allamin; Lis Tatin Hernidatiatin (Interdisciplinary Social Studies, 2026)
The development of electric motorcycles in Indonesia shows rapid growth until 2023, but has decreased in 2024. This condition indicates that there is a gap between increasing public environmental awareness and the realization of buying interest in environmentally friendly vehicles. One of the factors that is suspected to affect the buying interest is the implementation of Green Marketing by the company and the characteristics of Green Consumer in consumers. This research aims to analyze the influence of Green Marketing and Green Consumer on the Interest in Buying Electric Motorcycles in the community in Cirebon City, both partially and simultaneously. This research uses a quantitative approach with the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS). Data were collected through a Likert scale questionnaire to 115 respondents who were selected using purposive sampling techniques. The results of the study show that Green Marketing has a positive and significant effect on the Buying Interest of electric motorcycles, as well as Green Consumers which also have a positive and significant effect. Simultaneously, Green Marketing and Green Consumer were able to explain 69.6% of the variation in Buying Interest, with Green Marketing having a more dominant influence. The results of this study show that an effective green marketing strategy, supported by consumer environmental awareness, plays an important role in increasing buying interest in electric motorcycles.